2014
DOI: 10.1001/jama.2014.9645
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Early Administration of High-Dose Erythropoietin in Preterm Infants and Brain MRI Abnormality at Term-Equivalent Age

Abstract: clinicaltrials.gov Identifier: NCT00413946.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
5
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 39 publications
6
100
5
2
Order By: Relevance
“…This high‐dose rhEPO in rodents was equivalent to that in preterm infants given at a high dose of 1,000 to 2,500U/kg 20. Based on those results from neonatal rodent brain injury models, clinical studies showed that high‐dose rhEPO (2,500–3,000U/kg) administered after birth was well tolerated in preterm and term infants14, 20, 33, 37, 42 and conferred neuroprotection 16, 36. In a previous study using low‐dose rhEPO to prevent anemia in preterm infants, it was observed that preterm infants with rhEPO treatment also had significant neurodevelopmental improvement 38.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This high‐dose rhEPO in rodents was equivalent to that in preterm infants given at a high dose of 1,000 to 2,500U/kg 20. Based on those results from neonatal rodent brain injury models, clinical studies showed that high‐dose rhEPO (2,500–3,000U/kg) administered after birth was well tolerated in preterm and term infants14, 20, 33, 37, 42 and conferred neuroprotection 16, 36. In a previous study using low‐dose rhEPO to prevent anemia in preterm infants, it was observed that preterm infants with rhEPO treatment also had significant neurodevelopmental improvement 38.…”
Section: Discussionmentioning
confidence: 87%
“…EPO produced in the central nervous system7 is upregulated after insult and plays a role in neuroprotection 8, 9, 10, 11. Experimental studies have reported that rhEPO possesses neuroprotective properties in different neonatal brain injury animal models,12, 13 and clinical studies have shown that rhEPO treatment reduces brain injury and the incidence of neurological disabilities in infants 8, 14, 15, 16, 17. In addition, improved neurodevelopmental outcomes have been observed in preterm infants with anemia after rhEPO treatment 17, 18, 19, 20.…”
mentioning
confidence: 99%
“…58 Epo monotherapy, without hypothermia, may be useful for neonatal conditions other than HIE, such as perinatal stroke, 59 congenital heart disease, 60 and brain injury of prematurity. [61][62][63][64] This is the first clinical study of HIE that assesses biomarkers of efficacy to evaluate whether Epo provides additional neuroprotection to hypothermia. We found that Epo treatment was associated with significantly reduced severity of brain injury on MRI, specifically in the subcortical region (ie, the area that contains the basal ganglia, thalamus, and internal capsule).…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Leuchter et al 17 reported decreased gray and white matter injury in 77 of the erythropoietin-treated infants compared with 88 placebo-treated infants, and O'Gorman et al 18 reported improved white matter development as assessed by diffusion tensor imaging and tract-based spatial statistics in 24 of the erythropoietin-treated infants compared with 34 placebotreated infants. A US multicenter trial of high-dose erythropoietin for neuroprotection in 960 extremely low gestational age infants (PENUT [Preterm Epo Neuroprotection Trial]; NCT01534481) is ongoing, and neurodevelopmental outcomes are expected in ∼3 years.…”
Section: Figurementioning
confidence: 99%